Studi Terhadap Seorang Perempuan Sebagai Korban Revenge Porn di Pekanbaru - Abdul Munir; Wulan Junaini (SISI LAIN REALITA, 2020)
The need for the fulfillment of technology ang information is a necessity in modern life today. Increase sophisticate communication flow makes the distance relationship between a person and another be increasingly. In addition, adolescent relationship are increasingly rife and do not know the limits of new problems in social life. Many young people today who hang out and build the relationship without knowing the time and situation. In 2017 ago at Pekanbaru there was a case of revenge porn commited by a student at one private campus initials M against his girlfriend who had the initials B. after this incident, B feel the trauma and often unpleasant treatment, and even tends to lead to harassment by some of her friends on campus. At the first, B build relationship with her boyfriend the initials M with the good condition, but the over time B often get the treated violently by her boyfriend, example phisically violent, verbally violent, and sexually violent. Her boyfriend also recorded and distributed their sexs video to social media. From this case, the author will be analysis the case of revenge porn into feminist and victimology theory. This research also uses the descriptive and qualitative methods by taking interview data from various sources, such as B as the victim, mother of B, the friends B, observers, and related institutions. In this cases, the authors also giving the reccomendations so that in the future, the similar cases will not be repetaed.